Social Networks and (Political) Assimilation in the Age of Mass Migration - Costanza Biavaschi; Corrado Giulietti; Yves Zenou (Global Labor Organization (GLO), 2022)
This paper investigates the causal pathways through which ethnic social networks influence individual naturalization. Using the complete-count Census of 1930, we digitize information on the exact residence of newly arrived immigrants in New York City. This allows us to define networks with a granularity detail that was not used before for historical data - the Census block - and therefore to overcome issues of spatial sorting. By matching individual observations with the complete-count Census of 1940, we estimate the impact that the exogenous fraction of naturalized co-ethnics in the network observed in 1930 has on the probability of immigrants to acquire citizenship a decade later. Our results indicate that the concentration of naturalized co-ethnics in the network positively affects individual naturalization and that this relationship operates through one main channel: information dissemination. Indeed, immigrants who live among naturalized co-ethnics are more likely to naturalize because they have greater access to critical information about the benefits and procedures of naturalization.
Keywords: J61; J62; N32; Z1; 330; Social networks; assimilation; naturalization; migration